Systemic Modeling of Agent Coaction: A Catalog of Decentralized Coordinating Processes - Sudeikat, Jan (Electronic Communications of the EASST, 2010)
Taking inspiration from natural self-organizing systems is a successful strategy to solve computational problems in distributed systems. Faced with a particular problem, application designers have to identify an appropriate dynamical behavior and decide how to induce similar behavioral modes. In order to consolidate these ad-hoc activities to a systematic dynamical design method, we discuss and exemplify a behavioral modeling approach that describes the macroscopic behavior of agent-based software systems. This formalism is used to catalog the dynamic behavior of prominent examples of natural self-organizing systems. These here presented models represent generic, reusable templates for decentralized system adaptations that serve as analysis templates for application designs. A tailored programming model allows to supplement these templates in agent-based software applications with minimal intervention in the agent models.